(untitled) (Jurnal Ecosolum, 2021)
Sugarcane (Saccharum Officinarum L) is one of the potential plants and has sufficient economic values with an important role as a source of economic growth in Indonesia. Sugarcane land suitability index in Arasoe, Bone. Sugarcane plantations using a parametric approach and analyzing the relationship between land characteristics and sugarcane production at the study location. This research was performed in 9 (nine) unit lands produced from overlapping slope maps, soil type maps, and PT Arasoe sugarcane map with sugarcane production high (> 50 tons/ha), moderate (40-30 tons/ha), and low (<30 tons/ha). This research took place between July - November 2019. To calculate the land suitability index (IKL) used the parametric method with the Khiddir equation (1986), to evaluate the relationship between IKL and sugarcane productivity using Pearson correlation analysis. Research shows that the value of IKL ranges from 31.56 to 42.43 and classified according to marginal (S3) with limited factors are climate and base saturation. The relationship between IKL and sugarcane productivity was statistically significant as evidenced by the Pearson correlation coefficient r> 0.4 (p <0.05) which showed that along with the increase in IKL, sugarcane productivity also increased significantly.